Electronic Cigarette: The Influence of Lifestyle, Health Perspective and Product Characteristic to Switching Behaviour in Surabaya, Indonesia - Paramitha, Intan Tirzana; Mujanah, Siti; Fianto, Achmad Yanu Alif (International Journal of Economics (IJEC), 2025)
The purpose of this research is to understand the electronic cigarette user about their lifestyle profile, health perception, product experience and how this contribute to their switching behaviour from conventional cigarette to be e-cigarette user. This online survey with sample used consisted of 100 respondents in Surabaya. Indonesia - who are currently use electronic cigarette, as dual user or already fully switched from conventional cigarettes. Sampling was conducted randomly through an online questionnaire using a Likert scale. Data analysis was carried out using the Structural Equation Modeling (SEM) approach with the Partial Least Squares (PLS) methodology. The results of this research indicate that product experience use have significant and strong influence to the switching decision. Health perception also have significant and positive influence in switching behaviour, meanwhile the the Lifestyle apparently have weak influence to switching behaviour. The implication of this study can be used by business to tailor marketing communication strategy for middle-upper social segment where to emphasize more to the product experience and health benefit rather than lifestyle to support switching behaviour to electronic cigarettes from conventional cigarettes.